EDITORIAL: FACING THE APARTHEID ARCHIVE - Stevens, Garth; Laubscher, Leswin (PINS-Psychology in Society, 2025)
When Jacques Derrida (1998) wrote Archive fever in the mid-1990s, its seminal importance was almost immediately recognised across much of the disciplinary spectrum, from philosophy to cultural studies, and from history to literary studies, to name but a few. Where mainstream psychology is concerned, however, the reception was reminiscent of David Hume’s characterisation of his Treatise of human understanding, that it “fell dead-born from the press, without reaching such distinction as even to excite a murmur among the zealots” (2010: 3). What makes psychology’s neglect of this text, and many others like it, all the more puzzling, is not only that the full title, Archive fever: A Freudian impression, clues as apparent a psychological connection as any, but that the very content of the text suggests a wrestling with issues that are profoundly psychological – issues and dynamics such as memory inscription and iteration, identity, loss and mourning, the desire for origins and continuities, and various responsibilities, limitations and possibilities that derive from a theory of memory and the archive.